The Effectiveness of Sensory-Motor Integration on Clumsiness in Children with Nonverbal Learning Disabilities - Saeid Sadeghi; Forogh Mohammadian; Hamidreza Pouretemad; Hamidreza Hasanabadi (Vesnu Publications, 2017)
Introduction: One of the most important problems of children with nonverbal learning disabilities is clumsiness and poor coordination. This issue prevents children's academic achievement and socio-emotional development. This study aimed to evaluate the effectiveness of sensory-motor integration on clumsiness in children with nonverbal learning disabilities. Materials and Methods: The present study was performed through pre-test and post-test. For this purpose, 7 children with nonverbal learning disabilities (4 boys and 3 girls) in grades 2 to 5 of elementary school in Tehran, Iran, were selected using non-random sampling method. The Lincoln-Oseretsky motor scale was completed before and after the intervention and the data were analyzed using Wilcoxon test. Results: Sensory-motor integration had a positive significant effect on balance (P = 0.017), rough motor skills (P = 0.018), fine motor skills (P = 0.016), bilateral coordination (P = 0.012), and total clumsiness score (P = 0.016). Conclusion: The results showed that sensory-motor integration caused a significant difference in clumsiness in children with nonverbal learning disabilities and improved their motor skills in the four areas of balance, rough motor skills, fine motor skills, and bilateral coordination.